RESEARCH OF THE TRANSFORMATION OF CONSUMER BEHAVIOR IN THE FASHION MARKET - S.V. Zinchenko; E.M. Bijanova; A.D. Khusainova (Модели, системы, сети в экономике, технике, природе и обществе, 2022)
Background. At present, the issues of researching consumer behavior and analyzing customer experience in general are becoming more acute and relevant both in Russian and world practice. According to research, the average lifespan of fashion companies is shrinking. Often this is because many large and global players are large enough to quickly adapt to new trends and changing consumer behavior, they become uninteresting for today's consumers. The events of recent decades, global crises, the COVID-19 pandemic, the international political situation have led to a serious transformation of consumer experience in all markets, including the fashion market. The goal of the work is to research the transformation of consumer behavior in the fashion market. Materials and methods. In the process of research, methods of analysis and synthesis, comparison and generalization of information were used. Results. Identified consumer trends, new consumption patterns and consumer habits in the fashion market, the emergence of which is caused by global crises, digital technologies, generational change, causes a change in the business models of fashion companies and approaches to managing customer experience. Conclusions. To maintain a competitive position in the market, fashion companies need to analyze consumer behavior, trends and changes in consumer demand, identify new consumption patterns and change their work with clients. It becomes a prerequisite for successful business.